Correlation between neutrophil to lymphocyte and platelet to lymphocyte ratios and renal involvement in systemic lupus erythematosus in Central Vietnam - Nguyen, Hoang Thanh Van; Nguyen, Thanh Thu (Tạp chí Y Dược Huế, 2022)
Background: Systemic Lupus Erythematosus (SLE) is a complex autoimmune disease with diverse clinical manifestations and relapsing - remitting disease course. Nephritis is a major cause of morbidity and mortality in patients with lupus. Many clinical parameters and laboratory markers can be used to evaluate disease activity and nephritis. Neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) are positively associated with inflammatory disorders. Objectives: To evaluate the correlation between NLR and PLR in peripheral blood and renal involvement in systemic lupus erythematosus. Methods: 63 patients were diagnosed with SLE according to the criteria of the Systemic Lupus International Collaborating Clinics 2012 (SLICC 2012) and were treated at the Internal Medicine Department of Hue University of Medicine and Pharmacy Hospital, Thua Thien Hue province, in central Vietnam, from February 2020 to July 2021. This study included 41 SLE patients with lupus nephritis (LN) and 22 SLE patients without renal involvement. Results: The mean age of the study group was 31.67 ± 12.10. The most common age group was 21-50 years old, accounting for 69.8%. Females accounted for 90.5% and the female-to-male ratio stood at 9.5:1. Clinical and laboratory characteristics: acute cutaneous lupus 50.8%, subacute cutaneous lupus 11.1%, oral ulcers 27%, non - scarring alopecia 47.6%, arthritis 61.9%, pleural or pericardial effusion 30.2%, renal involvement 65.1%, neuropsychiatric damage 4.8%, anemia 81.0%, leukopenia 22.2%, neutropenia 11.1%, lymphopenia 41.3%, thrombocytopenia 15.9%, hemolytic anemia 15.9%, positive ANA antibody 61.9%, positive anti-ds DNA antibody 52.4%. Acute cutaneous lupus and arthritis in SLE patients without the nephritis group were higher than in the LN group (p < 0.05). Anemia, lymphopenia, thrombocytopenia, positive ANA, anti-ds DNA in the LN group were higher than SLE patients without nephritis (p < 0.05). SLE patients with LN had higher levels of NLR than those without nephritis. While PLR had no remarkable difference between these two groups. NLR was positively correlated with CRP , serum creatinine, and 24-hour urinary protein. PLR was positively correlated with the SLEDAI score. The best NLR to predict LN was 4.97 with a sensitivity of 51.2% and a specificity of 95.5% (AUC = 0.742, 95% CI, 0.617 - 0.866, p = 0.002). Conclusion: Most of the clinical manifestations in SLE patients according to SLICC 2012 criteria were lupus nephritis, arthritis, and acute cutaneous lupus. PLR was positively correlated with the SLEDAI score. NLR could predict renal involvement in SLE patients.